Measuring the unmeasurable: maternal piety scales - Hassan, Siti Aishah; Abdullah, Abdullah Seif; Mohd Ishak, Noriah; Langgulung, Hasan (Universiti Putra Malaysia Press, 2008)
The purpose of this study was to develop an instrument that measures maternal spiritual characteristics. Particularly, the instrument aims to measure a domain of spirituality which is commonly regarded as “the un-measurable” i.e. Maternal Piety. The study was conducted in two phases. The first phase was a longitudinal study of a focus group from an Islamic Integrated Primary School (IIPS). In, this phase Cronbach’s alpha was employed to assess the reliability index. Accordingly, Principal Component Analysis was employed to explore the underlying dimensions of Maternal Piety. The second phase was an ex-post facto study that involved 12 IIPS in the Klang Valley area. Confirmatory factor analysis (CFA) was utilized to examine the construct validity of the instrument. Finally, Structural Equation Modeling (SEM) was utilized to investigate the relationship between Maternal Piety (MP) and Maternal Quality Relationship (MQR) as supporting evidence for the criterion-related validity. The results provided evidence that the instrument achieved sound psychometrics properties. This instrument succeeded the standard Cronbach’s alpha > 0.70 for internal consistency and the proportion of variance explained was >0 50 % for the three dimensions of Maternal Piety. The goodness-of-fit measures GFI, AGFI, IFI, TLI, and CFI were > 0.90 and RMSEA was < 0.08 which were evidences for construct validity. Moreover, the findings supported the postulation that MP positively influenced MQR as evidence for the criterion-related validity. In short, Maternal Piety Scales is a reliable and valid instrument. From the practical standpoint, it suggests that spirituality is no longer remaining aloof in theoretical forms and neither exclusive for theologians only.